2018
DOI: 10.1038/bjc.2017.485
|View full text |Cite
|
Sign up to set email alerts
|

Randomised study shows that repeated self-sampling and HPV test has more than two-fold higher detection rate of women with CIN2+ histology than Pap smear cytology

Abstract: This corrects the article DOI: 10.1038/bjc.2017.85.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
80
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 38 publications
(84 citation statements)
references
References 45 publications
2
80
0
Order By: Relevance
“…We have previously shown in a smaller cohort study based on the follow‐up of women that were previously known to be HPV positive, that vaginal self‐sampling and using the FTA card is equally efficient as assisted sampling on the cervix for identification of HPV and histology defined high‐grade cervical lesions In the present study, a population‐based randomised study design was used to assess the efficiently of self‐sampling for detection of HPV and high‐grade cervical lesions. Recently we have also shown that repeated self‐sampling on FTA cards for HPV test detects more than two‐fold as many women with CIN2+ as Pap smear cytology . HPV typing results based on FTA cards shows consistent results across menstrual cycle phases and calendar time .…”
Section: Introductionmentioning
confidence: 67%
See 3 more Smart Citations
“…We have previously shown in a smaller cohort study based on the follow‐up of women that were previously known to be HPV positive, that vaginal self‐sampling and using the FTA card is equally efficient as assisted sampling on the cervix for identification of HPV and histology defined high‐grade cervical lesions In the present study, a population‐based randomised study design was used to assess the efficiently of self‐sampling for detection of HPV and high‐grade cervical lesions. Recently we have also shown that repeated self‐sampling on FTA cards for HPV test detects more than two‐fold as many women with CIN2+ as Pap smear cytology . HPV typing results based on FTA cards shows consistent results across menstrual cycle phases and calendar time .…”
Section: Introductionmentioning
confidence: 67%
“…There was a higher participation rate in the SS arm, in line with our recent published study (women aged 30-49) showing a higher participation rate for women invited to self-sampling as compared to those invited for Pap smear cytology testing. 22 The lower participation in the AS arm can be explained by the fact that some women were wrongly offered the Pap smear cytology instead of the HPV test, since the transition to the new strategy started at the same time as the present study. In addition, when summarising data from the regular invitation system we found that fewer women in the AS arm than expected received an invitation, and those women were excluded as not eligible, which could have affected the calculated participation rate for the AS arm.…”
Section: Participationmentioning
confidence: 77%
See 2 more Smart Citations
“…To increase the specificity of screening, and distinguish between transient and persistent HPV infections, the HPV-test can be repeated 4 -6 months after the primary screening test. This has been shown to reduce the number of HPV infections requiring management by about 40% (11,12). An alternative way is to combine the HPV test with additional biomarkers indicating the persistence of infection or identifying early signs of cervical dysplasia (2,3).…”
Section: Graphical Abstractmentioning
confidence: 99%